Pengaruh Lingkungan Mikroklimat terhadap Produktifitas Susu Sapi Perah Freisian holstein (FH) di Peternakan Sapi Terpadu (PESAT) KPC - Ardiansyah Ardiansyah; Apdila Safitri; Nugroho Dewanto (Musamus Journal of Livestock Science, 2023)
Response of Livestock performance was determined by genetic and environmental factors. FH of dairy cow can produce milk higher than other dairy cows according to its genetic ability. This is supported by environmental factors such as the fulfillment of nutrients needs of feed and microclimate in the area of livestock. This study evaluated the effect of microclimate environmental factors on milk dairy cattle productivity in PESAT using multiple regressions. Microclimate data (air temperature, RH, rainfall, wind speed, and solar radiation) were taken from the observation of PT Kaltim Prima Coal weather station located at M1 near PESAT in 2016-2017. The PESAT milk production data was taken from 2016-2017. Microclimate affects 63.3% (P<0.05) of dairy milk production refers to equation of Milk production = -226.079 -25.317 x Temperature + 8.699 x RH + 34.732 x Rainfall -37.575 x Wind Speed + 2.327 x Solar Radiation. Microclimates have a strong positive relation to milk production of 0.796. Decreasing in temperature and wind speed, Increasing of RH, rain, and solar radiation will increase the milk production. Microclimate manipulation can be done, but it will require high cost investment.